Reproducibility and Agreement of Anterior Segment Parameter Measurements Obtained Using the CASIA2 and Spectralis OCT2 Optical Coherence Tomography Devices. Issue 11 (November 2017) - Xu, Benjamin Y.; Mai, Derek D.; Penteado, Rafaella C.; Saunders, Luke; Weinreb, Robert N.
Abstract : Purpose: To assess the reproducibility and agreement of measurement values obtained from the Tomey CASIA2 and Heidelberg Spectralis OCT2 anterior segment optical coherence tomographic devices. Methods: Twenty eyes from 10 subjects ranging from age 28 to 45 years with no history of eye conditions or intraocular surgery were included. Two scans were obtained with each device in a standardized dark room environment after a period of dark adaptation. One anterior segment optical coherence tomography image along the horizontal (temporal nasal) meridian was analyzed per eye and per scan. Lens vault, pupil diameter, anterior chamber width, angle opening distance, trabecular iris space area, and scleral spur angle were measured using manufacturer-provided image analysis programs. Intraclass correlation coefficient (ICC) values, coefficients of variation, and Bland-Altman plots were computed to assess the intradevice correlation and interdevice agreement of measurement values. Results: There was excellent intradevice reproducibility of measurement values for both the CASIA (ICC range, 0.86 to 0.99) and Spectralis (ICC range, 0.79 to 1.00). There was also excellent interdevice correlation of measurement values (ICC range, 0.78 to 0.93) for all parameters except anterior chamber width (ICC 0.20). Linear regression models and Bland-Altman plots showed that this relationship was strongest when measurement values were small. Conclusions: There is excellent intradevice reproducibility and good interdevice agreement of anterior segment parameter measurement values for the CASIA2 and Spectralis OCT2. However, the measurements obtained with each device should not be considered interchangeable.